The Application of Biomaterials to Tissue Engineering Neural Retina and Retinal Pigment Epithelium. Issue 23 (2nd September 2018) - Hunt, Nicola C.; Hallam, Dean; Chichagova, Valeria; Steel, David H.; Lako, Majlinda
Abstract: The prevalence of degenerative retinal disease is ever increasing as life expectancy rises globally. The human retina fails to regenerate and the use of human embryonic stem cells (hESCs) and human‐induced pluripotent stem cells (hiPSCs) to engineer retinal tissue is of particular interest due to the limited availability of suitable allogeneic or autologous tissue. Retinal tissue and its development are well characterized, which have resulted in robust assays to assess the development of tissue‐engineered retina. Retinal tissue can be generated in vitro from hESCs and hiPSCs without biomaterial scaffolds, but despite advancements, protocols remain slow, expensive, and fail to result in mature functional tissue. Several recent studies have demonstrated the potential of biomaterial scaffolds to enhance generation of hESC/hiPSC‐derived retinal tissue, including synthetic polymers, silk, alginate, hyaluronic acid, and extracellular matrix molecules. This review outlines the advances that have been made toward tissue‐engineered neural retina and retinal pigment epithelium (RPE) for clinical application in recent years, including the success of clinical trials involving transplantation of cells and tissue to promote retinal repair; and the evidence from in vitro and animal studies that biomaterials can enhance development and integration of retinal tissue. Abstract : The potential of biomaterial scaffolds to enhance generation of hESC/ hiPSC‐derived neural retina and retinal pigment epithelium is demonstrated in studies. This review outlines the structure of retina, retinal diseases, clinical trials and treatments, along with evidence from in vitro and in vivo studies that biomaterials can enhance by the development and integration of retinal tissue.